2019
DOI: 10.1182/blood-2019-127586
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Release Syndrome As a Rare Complication of Nivolumab: A Case Report

Abstract: Immune checkpoint inhibitors such as CTLA-4 and PD-1 inhibitors mediate T-cell induced tumor cell destruction by blocking malignant cells' ability to negatively regulate T cell activity. In addition to its anti-tumor effect, checkpoint inhibition can lead to loss of maintenance of self-tolerance, leading to immune-mediated adverse events (irAEs). These events can affect any organ, with pneumonitis, hepatitis, and colitis among the most commonly reported events. A rare and life-threatening reported side effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Third, in several cases COVID-19 was associated with a cytokine release syndrome (CRS) due to a massive secretion of pro-inflammatory cytokines, and severe, acute systemic symptoms involving the IL-6-signalling pathway 6 . Similar cytokine release syndromes have been observed under checkpoint inhibition 7 . This might explain a tendency for more severe symptoms, a high rate of hospitalizations 8 and a worse outcome as reported by Robilotti et al 9 However, it remains unclear if patients on checkpoint-inhibitor treatment are truly more susceptible for a cytokine release syndrome due to COVID-19.…”
supporting
confidence: 74%
“…Third, in several cases COVID-19 was associated with a cytokine release syndrome (CRS) due to a massive secretion of pro-inflammatory cytokines, and severe, acute systemic symptoms involving the IL-6-signalling pathway 6 . Similar cytokine release syndromes have been observed under checkpoint inhibition 7 . This might explain a tendency for more severe symptoms, a high rate of hospitalizations 8 and a worse outcome as reported by Robilotti et al 9 However, it remains unclear if patients on checkpoint-inhibitor treatment are truly more susceptible for a cytokine release syndrome due to COVID-19.…”
supporting
confidence: 74%
“…CRS has been observed to be triggered by several monoclonal antibodies, systemic interleukin-2, and more recently, the CD19-CD3 chimeric antigen receptor Tcell therapy (35). A few case reports have detailed lifethreatening CRS in patients after the administration of ICIs, with occurrences ranging from cycles 1 to 17 (36)(37)(38)(39). The culprit medications were anti-PD-1 and anti-LAG-3.…”
Section: Discussionmentioning
confidence: 99%
“…The culprit medications were anti-PD-1 and anti-LAG-3. Alexander et al reported the case of a patient with stage IV melanoma who received nivolumab on cycle 17 and had a CRS episode; it was controlled by tocilizumab initially, but the patient died 6 weeks later because of another CRS episode (39). Seth et al also reported a patient with alveolar soft part sarcoma who received nivolumab and had a CRS event that was resolved by tocilizumab and corticosteroids (38).…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] In the post-platinum setting, pembrolizumab remains the preferred agent, [18] with other agents (atezolizumab, nivolumab, avelumab, durvalumab) included in treatment guidelines but not supported by randomized, phase III trials. [19] , [20] , [21] , [22] , [23] …”
Section: Systemic Therapy Considerations In the Covid-19 Eramentioning
confidence: 99%
“…[ 20 , 21 ] At the same time, ICI administration itself has also been reported to cause a state of “immune hyperactivation”, whereby patients can present with cytokine release syndrome (CRS) ( Figure 1 ). [22] , [23] , [24] , [25] , [26] , [27] , [28] This massive release of cytokines can result in symptoms ranging from mild constitutional symptoms (fever, malaise, and myalgias) to severe end-organ damage. A retrospective study from China of 150 patients with confirmed COVID-19 infection showed that elevated ferritin and IL-6 were predictors of death, suggesting that COVID-19 induced immune activation may be a contributing factor in increasing mortality.…”
Section: Systemic Therapy Considerations In the Covid-19 Eramentioning
confidence: 99%